Hydrothermal effects of using two twisted tape inserts in a parabolic trough solar collector filled with MgO-MWCNT/thermal oil hybrid nanofluid. (October 2021) - Alnaqi, Abdulwahab A.; Alsarraf, Jalal; Al-Rashed, Abdullah A.A.A.
Abstract: Despite the studies that have been done on boosting the performance of solar collectors, their efficiency is still not acceptable and therefore, it is necessary to provide new solutions to augment their performance. Therefore, in this numerical contribution, the thermal-hydraulic performance of parabolic trough solar collectors (PTSCs) has been improved by using two twisted tapes. The MgO-MWCNT (80%:20%)/thermal oil hybrid nanofluid is considered as the coolant. The numerical work is performed using the two-phase model. The effects of geometrical parameters, Reynolds numbers (Re), width and rotation directions of twisted tapes and nanoparticle volume fraction on the hydrothermal aspects of the PTSC are investigated. The most significant result obtained from the present study is to propose the best conditions in terms of geometry and volume fraction of nanoparticles employed for the practical utilization of twisted tape in PTSCs. The use of LCRW model at turbulator diameter of 15 mm filled with nanofluid at nanoparticle volume fraction of 2% was suggested as the optimum PTSC for Re < 30, 873, while usage of LWRC model at turbulator diameter of 15 (mm) filled with nanofluid at nanoparticle volume fraction of 2% was suggested as the optimum PTSC for Re > 30, 873.